Moses like David: prototypes in the deuteronomistic history - Joseph, Alison L. (Hebrew Union College annual, 2019)
The historiographical style of the deuteronomistic historian (Dtr) has often been identified as unique within the Hebrew Bible. One of the tendencies of Dtr is to construct characters who fit into specific prototypes. This is quite clear in the Book of Kings where the kings of Israel and Judah, good and bad, are cast in the model of David and Josiah. This is also true for the position of prophet. In Deuteronomy 18:15-22, Dtr establishes a “prophetic prototype” in the likeness of Moses, but it is not employed beyond this passage. This article will explore the use of the Davidic and prophetic prototypes in the Deuteronomistic History (DtrH) and will suggest why the prophetic model is proposed but not applied.